The Effect of The Ink Coffee Grounds Material for Black Colour in Screen Printing - Yuniarti, Endang (Kreator, 2024)
The carbon content in coffee grounds can be utilized as a base material or organic pigment in making ink. Organic pigments are made by refining and reducing the particle size of coffee grounds using a screen mesh, and mortar and pestle. The process of making ink is done by mixing coffee grounds with ink-making materials such as distilled water, gum arabic, and arrowroot flour. The process of making this ink is  carried out with 4 variations of the composition of coffee grounds, which are  15, 20, 25, and 30 grams. The purpose of this study is to  determine the effect of variations in the composition of coffee grounds on the physical properties of the ink, namely viscosity, and on print quality, such as density and L*a*b. The results showed that the addition of coffee grounds pigments affected the density, L*a*b, and viscosity values. The higher the composition of coffee grounds, the higher the density, L*a*b, and ink viscosity values.